Clustered Regularly Interspaced Short Palindromic Repeats-Associated Proteins13a combined with magnetic beads, chemiluminescence and reverse transcription-recombinase aided amplification for detection of avian influenza a (H7N9) virus - Xu, Hongpan; Peng, Lijun; Wu, Jie; Khan, Adeel; Sun, Yifan; Shen, Han; Li, Zhiyang (Frontiers in Bioengineering and Biotechnology, 2023)
Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) and Clustered Regularly Interspaced Short Palindromic Repeats-Associated Proteins (CRISPR-Cas) have promising prospects in the field of nucleic acid molecular diagnostics. However, Clustered Regularly Interspaced Short Palindromic Repeats-based fluorescence detection technology is mainly hindered by proteins with conjugated double bonds and autofluorescence, resulting in high fluorescence background, low sensitivity and incompatible reaction systems, which are not conducive to automatic clinical testing. Chemiluminescence (CL) detection technology has been applied mainly owing to its greatly high sensitivity, as well as low background and rapid response. Therefore, we developed a rapid, ultrasensitive and economical detection system based on Clustered Regularly Interspaced Short Palindromic Repeats-Clustered Regularly Interspaced Short Palindromic Repeats-Associated Proteins 13a combined with magnetic beads (MBs) and chemiluminescence (CL) (Cas13a-MB-CL) to detect Influenza A (H7N9), an acute respiratory tract infectious disease. The carboxyl functionalized magnetic beads (MBs-COOH) were covalently coupled with aminated RNA probe while the other end of the RNA probe was modified with biotin. Alkaline phosphatase labeled streptavidin (SA-ALP) binds with biotin to form magnetic beads composites. In presence of target RNA, the collateral cleavage activity of Cas13a was activated to degrade the RNA probes on MBs and released Alkaline phosphatase from the composites. The composites were then magnetically separated followed by addition of ALP substrate Disodium 2-chloro-5-4-methoxyspiro [1,2-dioxetane-3,2′-(5′-chloro) tricyclo (3.3.1.13,7) decan]-4-yl-1-phenyl phosphate (CDP-star), to generate the chemiluminescence signal. The activity of Associated Proteins 13a and presence of target RNA was quantified by measuring the chemiluminescence intensity. The proposed method accomplished the detection of H7N9 within 30 min at 25°C. When combined with Reverse Transcription- Recombinase Aides Amplification (RT-RAA), the low detection limit limit of detection was as low as 19.7 fM (3S/N). Our proposed MB-Associated Proteins 13a-chemiluminescence was further evaluated to test H7N9 clinical samples, showing superior sensitivity and specificity.